2008
DOI: 10.1111/j.1399-6576.2007.01572.x
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of fluid absorption with nitrous oxide during transurethral resection of the prostate

Abstract: The N(2)O method does not require forced breath sampling and was successfully apply clinically. However, there was a dose-dependent difference in result between the ethanol and N(2)O methods, which markedly separated the limits of agreement for a wider range of fluid absorption events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…The intravascular absorption of irrigation fluid during TURP has been shown to be approximately 700 ml. [9] However, studies have demonstrated no significant intravascular absorption of irrigation fluid with PVP. [1012] Thus for men with significant cardiovascular morbidity, in whom an increase in intravascular volume could precipitate cardiac failure, PVP potentially represents a safer option to conventional TURP.…”
Section: Discussionmentioning
confidence: 99%
“…The intravascular absorption of irrigation fluid during TURP has been shown to be approximately 700 ml. [9] However, studies have demonstrated no significant intravascular absorption of irrigation fluid with PVP. [1012] Thus for men with significant cardiovascular morbidity, in whom an increase in intravascular volume could precipitate cardiac failure, PVP potentially represents a safer option to conventional TURP.…”
Section: Discussionmentioning
confidence: 99%
“…Whenever glycine or ethanol is recognized as potentially toxic in the setting of TURP, alternative irrigants should be used. Some authors have suggested the use of expectedly safer irrigation fluids, such as glucose solution [1] or the use of tracers different from ethanol, such as nitrous oxide [17]. In the mean time, surgeons should be made aware that severe complications of TUR syndrome, such as acute liver failure, may occur.…”
Section: Discussionmentioning
confidence: 99%
“…The intravascular absorption of irrigation fluid during TURP has been shown to be approximately 700mL [3]. However, studies have demonstrated no significant intravascular absorption of irrigation fluid with PVP [4][5][6].…”
Section: Discussionmentioning
confidence: 99%